SURFACE AND SUBSURFACE WEED SEED EMERGENCE STUDIES IN PUDDLED RICE AS INFLUENCED BY IRRIGATION AND WEED MANAGEMENT OPTIONS - T. RAMPRAKASH; S. NARENDER REDDY, KESHAVAMURTHY, M. MADHAVI, G. PRATHIBA (The Journal of Research, PJTSAU, 2023)
An experiment was conducted to study the effect of irrigation and weed management practices on the emergence of weed seed bank at college farm situated in College of Agriculture, PJTSAU, Hyderabad, during kharif 2019 and 2020. The experiment consisted of two main plot treatments and nine subplot treatments laid out in Split plot design replicated thrice. Two irrigation practices (Alternate wetting and drying irrigation and continuous submergence) and nine weed management practices. Pretilachloar 50 EC 660 g ha-1(PE) fb mechanical weeding twice, pyrazosulfuron ethyl + pretilachloar 6.15 GR 615 g ha-1 (PE) fb penoxsulam + cyhalofop p butyl 6.12 OD 125 g ha-1 (POE), orthosulfamuron + pretilachloar 6.6 GR 600 g ha-1 (PE) fb mechanical weeding twice, penoxsulam + butachloar 39.77 SE 820 g ha-1 (PE) fb mechanical weeding, flucetosulfuron 10 % WG 25 g ha-1 (Early PoE) fb mechanical weeding, bispyribac sodium + 2, 4-D sodium salt 56.3 SP 703.75 g ha-1 (PoE) fb mechanical weeding once, florpyrauxifen benzyl + cyhalofop p butyl 12 EC 150 g ha-1 (PoE) fb mechanical weeding once, hand weeding twice and unweeded control. The irrigation practices not influenced the emergence of different species of weeds at surface and subsurface soil as well as total number of weeds. With respect to weed managements, significantly lowest in emergence of different species of weeds recorded in hand weeding treatment, whereas higher emergence of weeds was recorded in unweeded control.